Rapid Acquisition and Fielding for Information Assurance and Cyber Security in the Navy - Porche III, Isaac R. (RAND Corporation, 2012)
The U.S. Navy requires an agile and adaptable acquisition process that can field new information technology capabilities and services in relatively short and responsive time frames. A RAND study sought to identify ways to accelerate or bypass the traditional acquisition process in response to the unique demands of information technology and cyber programs.